Tumor cell-intrinsic PD-1 promotes Merkel cell carcinoma growth by activating downstream mTOR-mitochondrial ROS signaling - Martins, Christina; Rasbach, Erik; Heppt, Markus V.; Singh, Praveen; Kulcsar, Zsofi; Holzgruber, Julia; Chakraborty, Asmi; Mucciarone, Kyla; Kleffel, Sonja; Brandenburg, Anne; Hoetzenecker, Wolfram; Rahbari, Nuh Nabi; et al. (Science advances, 2024)
Merkel cell carcinoma (MCC) is a rare and aggressive skin cancer. Inhibitors targeting the programmed cell death 1 (PD-1) immune checkpoint have improved MCC patient outcomes by boosting antitumor T cell immunity. Here, we identify PD-1 as a growth-promoting receptor intrinsic to MCC cells. In human MCC lines and clinical tumors, RT-PCR-based sequencing, immunoblotting, flow cytometry, and immunofluorescence analyses demonstrated PD-1 gene and protein expression by MCC cells. MCC-PD-1 ligation enhanced, and its inhibition or silencing suppressed, in vitro proliferation and in vivo tumor xenograft growth. Consistently, MCC-PD-1 binding to PD-L1 or PD-L2 induced, while antibody-mediated PD-1 blockade inhibited, protumorigenic mTOR signaling, mitochondrial (mt) respiration, and ROS generation. Last, pharmacologic inhibition of mTOR or mtROS reversed MCC-PD-1:PD-L1-dependent proliferation and synergized with PD-1 checkpoint blockade in suppressing tumorigenesis. Our results identify an MCC-PD-1-mTOR-mtROS axis as a tumor growth-accelerating mechanism, the blockade of which might contribute to clinical response in patients with MCC.
Veröffentlicht: 19. Januar 2024
Gesehen am 01.08.2024